The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2147/ijgm.s135305
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of tuberculosis treatment and its predictors among HIV infected patients in southwest Ethiopia

Abstract: BackgroundCo-infection with HIV challenges treatment of tuberculosis (TB) and worsens the outcome. This study aimed to assess the outcome of TB treatment and its predictors among HIV infected patients at Mizan-Tepi University Teaching Hospital (MTUTH), Ethiopia.MethodsMedical records of 188 TB/HIV co-infected patients who attended the TB clinic of MTUTH from September 2012 to December 2015 were reviewed from March 14 to April 1, 2016. The primary endpoints of the study were treatment outcome of TB and its pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 18 publications
(29 reference statements)
4
19
5
1
Order By: Relevance
“…But, the other studies done in other parts of Ethiopia [15,20] and China [27] reported as there is no significant difference between treatment success rate and type of TB. According to studies conducted at Jinka General Hospital [21], Afar [28] and another study done by Kefale et al at Southwest Ethiopia [29]; TB/HIV co-infection was found to be a predictor for unsuccessful treatment outcome, which is similar to the present study.…”
Section: Discussionsupporting
confidence: 90%
“…But, the other studies done in other parts of Ethiopia [15,20] and China [27] reported as there is no significant difference between treatment success rate and type of TB. According to studies conducted at Jinka General Hospital [21], Afar [28] and another study done by Kefale et al at Southwest Ethiopia [29]; TB/HIV co-infection was found to be a predictor for unsuccessful treatment outcome, which is similar to the present study.…”
Section: Discussionsupporting
confidence: 90%
“…The overall successful TB treatment outcome in this study was 78.6%. Our result is higher than that of previous studies conducted in Africa (Ethiopia 28.9% [11], 30.3% [12], 70.8% [13], Nigeria 48.8% [10], Ghana 64.0% [14] and Cameroon 60.8% [15]) and elsewhere (Malaysia 53.4% [16]). This dissimilarity might be due to the difference in number of study participants involved in the various studies.…”
Section: Discussioncontrasting
confidence: 87%
“…In relation to cohort and case–control studies, the total NOS scores ranged from 5 to 9, signifying included studies were of good quality. A score of 5 was recorded in a case–control49 and a retrospective cohort study,50 a score of 7 was found in one retrospective51 and another prospective cohort study,52 a score of 8 was found in four studies (two prospective cohort53 54 and two retrospective cohort studies,55 56 while each of the remaining 16 studies scored 9 (see online supplementary table 3). With respect to risk of bias in RCTs using the Cochrane’s collaboration tool, we found low risk of bias on the selection domain for the RCTs57–60 except in one RCT60 where it was high (see online supplementary figure 1).…”
Section: Resultsmentioning
confidence: 99%